Current trends of clinico-radiological findings, management and outcomes of chest trauma patients in a tertiary health care hospital in Western India - Shah, Dharmendra K.; Patel, Ashish H.; Chaudhary, Shivani R.; Sharma, Bhavya; Vaghani, Tejas B. (International Surgery Journal, 2022)
Background: There has been a rapidly rising trend of trauma cases, especially chest trauma; necessitating an in-depth study of its complications and management. Methods: We have studied 120 patients presenting to our emergency department for the demographics and etiology of their injury and recorded the results and outcomes of their radiological and clinical investigations and management protocol. Results: Middle aged men were the primary victims of chest trauma, mostly having blunt injuries and presenting with respiratory distress. A range of pleural and visceral injuries were seen like hemothorax, pneumothorax, flail chest; the mainstay of treatment for them being minimally invasive tube thoracostomy. We encountered a low mortality rate of 1.66%. Conclusions: Rapid intervention and resuscitation for all trauma cases prove to be lifesaving, amongst which focus on thoracic injuries must be primary. Ever increasing incidences of polytrauma cases indicate the requirement of strict vigilance and prevention of road traffic accidents.